Tumor Interstitial Fluid Formation, Characterization, and Clinical Implications - Wagner, Marek; Wiig, Helge (Frontiers in Oncology, 2015)
The interstitium, situated between the blood and lymph vessels and the cells, consists of a solid or matrix phase and a fluid phase, together constituting the tissue microenvironment. In the present review we focus on the interstitial fluid phase of solid tumors (TIF), i.e. the fluid bathing the tumor and stroma cells, also including immune cells. This is a component of the internal milieu of a solid tumor that has attracted regained attention. Access to this compartment may provide important insight into how tumors develop and how they respond to therapy. TIF is formed by transcapillary filtration, and since fluid is not readily available we discuss available techniques for TIF isolation, results from subsequent characterization and implications of recent findings with respect to transcapillary fluid balance and uptake of macromolecular therapeutic agents. It has recently been shown that local gradients exist in signaling substances from neoplastic tissue to plasma that may provide new insight into the biology of tumors. The emergence of sensitive proteomic technologies has made the interstitial fluid compartment in general, but that of tumors in particular, a highly valuable source for tissue specific proteins that may serve as biomarker candidates. Potential biomarkers will appear locally at high concentrations in the tissue of interest and will eventually appear in the plasma where they are diluted. Access to fluid that reliably reflects the local microenvironment enables us to identify substances that can be used in early detection and monitoring of disease.